Counseling on Clean and Healthy Living Behavior (PHBS) and Handwashing as the First Step Towards Improving the Quality of Public Health - Nurhayati; Akbar, Nurlina; Saputri, Linda Hardianti (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2020)
PHBS is short for Clean and Healthy Lifestyle. While the understanding of PHBS is all healthbehaviors carried out because of personal awareness so that the family and all members areable to help themselves in the health field and have an active role in community activities..Counseling material delivered about PHBS and how to wash hands on elementary and juniorhigh school students. This activity was carried out at the Elementary School Parang in LannaVillage with lecture, discussion and simulation methods. The results of this activity are studentsunderstanding about clean and healthy living behavior (PHBS) and how to wash hands properly, where students are able to answer questions given after health education and are able to practice independently how to wash hands properly and right. In addition, students participated in the activity enthusiastically so that it was the beginning to improve their patterns and lifestyle to be healthier.